The prop's the thing : stage properties reconsidered - Curry, Jane Kathleen (Theatre symposium, 2010)
Stage properties are an often-ignored aspect of theatrical productions, in part because their usage is meant to be seamlessly integrated into the performance instead of a focal point for the audience. However, a skillfully used prop can augment the action, just as a malfunctioning prop can destroy the illusion of the scene. The essays in "Theatre Symposium: Volume 18" approach the subject of stage props from many angles, and include examinations of props in contemporary and historical productions, explorations of the cultural significance of specific props, and arguments about the